The role of orthodox jurisprudence in dealing with domestic violence against women in Iran - Tizro, Zahra (La camera blu. Rivista di studi di genere, 2014)
This paper is concerned with the structure of power/knowledge in the orthodox Islamic discourses (as the mainstream discourse) in Iran, and the interrelationship between power, violence, and sexuality both theoretically and empirically. In the theoretical section of this study I employ a novel approach based on the economic theory of contract, in order to shed light on the internal logic of the Islamic formulation of marriage, how it is organised around a critical transaction of sexual submission for economic protection, and how this simple formulation may pave the way for violence against women, which turns into a source of perpetual tension in contemporary Iranian society. Empirically, drawing on fieldwork among 62 women, men and judicial officials in Gilan province (north Iran), this paper aims to report and reflect on the judicial official‟s narratives on marriage, marital relationship within the context of Islamic marriage and associated discourses of sexuality and violence.